Anti-Bullying Education As A Character Education Effort To Prevent Violence Among Students - Daulat Nathanael Banjarnahor; Sepriandison Saragih; Firinta Togatorop; Jan Sardo Pratama Purba (International Journal of Community Service (IJCS), 2024)
Bullying remains a serious problem in many schools in Indonesia. In general, data from the UN Children's Fund (UNICEF), released in 2021, indicates that approximately 30% of students have experienced bullying at school. The prevalence of bullying tends to make children who are victims feel afraid, isolated, and stressed, which negatively impacts their mental health and academic performance. Bullying cases in schools in Indonesia are quite concerning. The Indonesian Child Protection Commission (KPAI) recorded 17 cases of physical violence in 2021, resulting in six student deaths and one paralysis. This Community Service (PkM) activity aims to educate the academic community of Muhammadiyah 55 Kandangan Private Middle School so they understand the dangers of bullying and understand character education from an early age as a way to prevent bullying in and outside of school. The results obtained through the implementation of the PkM activity are that the students of Muhammadiyah 55 Kandangan Private Middle School have a better understanding of the meaning, types, and dangers of Bullying, as well as character education efforts as the best way to reduce and prevent Bullying at school and outside of school. The school and the PkM Team have almost the same views and suggestions, namely that there is a need for further activities in other forms, for example a Workshop within the framework of the Anti -Bullying School strengthening project